Coexistence Between Migrant Agro-pastoralists and Farmers in Kilombero Valley, Tanzania: Does Identity Matter? - Msinde, John (Tanzania Journal for Population studies and Development, 2026)
Migration among agro-pastoralists has led to resource competition which has resulted in deadly conflicts with communities in destination areas. The identity of agro-pastoralists is a key factor in coexistence, as it can lead either to peaceful coexistence, or to further contradictions. This article uses a case study of the Kilombero Valley, Tanzania, to examine the space of identity in the coexistence between two groups. Focus group discussions, in-depth interviews, and transect walks were employed to collect data from a purposively selected sample of migrant agro-pastoralists and farmers. The findings reveal a mixed understanding of ‘migrant’ as a social label. This label conceals the identities of the Sukuma, foreigners, corrupt individuals, and witches that prevail in the study area. The findings further show that identity is structured within conflict-mediating processes and institutions. Identity perpetuates conflicts and affects coexistence. Hence, coexistence in the Kilombero Valley in particular, and Tanzania in general, should be understood from the prism of social identity and not exclusively from a resource-competition viewpoint. This more nuanced approach to deconstructing the co-existence between migrant agro-pastoralists and farmers is relevant in formulating policies that reduce tensions between two groups that live side by side.